ANALISIS VARIASI BAHASA RAGAM JURNALISTIK DALAM KORAN MALUT POST - Anwar Nada; Riska H Riani (Universitas Khairun, 2021)
The purpose of this study is to describe the language variations contained in the opinion rubric newspaper and the factors that infuence language variationin the opinion rubric newspaper at the Malut Post Office, Ternate City. The cause of language variatation in the Malut Post newspaper, Ternate City. The source of the data used is an opinion rubric at te Malut Post office. Data collection techniques used are observation, interviews, and documentation. The data analysis techniques used are data reduction, data presentation, and the conclusion drawing stage. This research refers to the use of language variations in terms of formality, which consists of frozen variety, standard variety, business variety, relaxed variety, and familliar variety. Based on the results of research on the use of language variation in the opinion rubric newspaper in 6 texts in the opinion rubric newspaper at the Malut Post Office in Ternate City, it was found that language variatations werw 1) frozen variety 6, 2) standard variety 29, 3) business variety 27, 4) relaxed variety 10, 5) familliar variety 4. Based on the results of data analysis, it can be seen how the use of language variations in terms of formality in the opinion rubrics editions 5, 10, 15 january 2021 are very many and various variations are used by the outhor. It can also be seen that the use of language variations in sentences and words written is also different because it is caused by the background of the author who was sent to the editing office at the Malut post. Furthermore, the factors influence the language variation are found in the background of the outhor who thearticle because the authors of this opinion rubric are mostly from public, students, and activis.